2018
DOI: 10.1021/acs.biochem.7b01284
|View full text |Cite
|
Sign up to set email alerts
|

Hexamerization of Geranylgeranylglyceryl Phosphate Synthase Ensures Structural Integrity and Catalytic Activity at High Temperatures

Abstract: The cell membranes of all archaea contain ether lipids, and a number of archaea are hyperthermophilic. Consequently, the enzymes that catalyze the synthesis of membrane ether lipids had to adopt to these rough conditions. Interestingly, the enzyme that establishes the first ether bond in these lipids, the geranylgeranylglyceryl phosphate synthase (GGGPS), forms hexamers in many hyperthermophilic archaea, while also dimeric variants of this enzyme exist in other species. We used Methanothermobacter thermautotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 39 publications
(84 reference statements)
2
55
0
Order By: Relevance
“…Interestingly, the crystal structure of MtGGGPS revealed a hexamer that can be described as a trimer of dimers. Several other group II archaeal GGGPS enzymes have been identified as forming hexamers via static light-scattering experiments (Peterhoff et al, 2014;Linde et al, 2018). The quaternary structure of the MtGGGPS dimer is identical to that of the TvGGGPS dimer.…”
Section: Quaternary Structure Of Gggps and Ancestral State Reconstrucmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the crystal structure of MtGGGPS revealed a hexamer that can be described as a trimer of dimers. Several other group II archaeal GGGPS enzymes have been identified as forming hexamers via static light-scattering experiments (Peterhoff et al, 2014;Linde et al, 2018). The quaternary structure of the MtGGGPS dimer is identical to that of the TvGGGPS dimer.…”
Section: Quaternary Structure Of Gggps and Ancestral State Reconstrucmentioning
confidence: 99%
“…Mutagenesis experiments revealed that replacing Trp141 in MtGGGPS with an alanine residue results in disruption of the hexamerization interface, favoring formation of the dimer. Furthermore, differential scanning calorimetry and fluorimetry experiments indicate that the MtGGGPS hexamer has a significantly higher thermostability relative to the dimer and monomer (Linde et al, 2018). Oligomerization is a common adaptation of thermophilic proteins, along with an increased number of disulfide bonds, increased salt-bridging and increased surface charges (Reed et al, 2013).…”
Section: Quaternary Structure Of Gggps and Ancestral State Reconstrucmentioning
confidence: 99%
See 2 more Smart Citations
“…This enzyme is involved in the biosynthesis of ether membrane lipids that are prototypical for Archaea and catalyzes the formation of an ether bond between glycerol 1-phosphate and geranylgeranyl diphosphate (Chen et al, 1993;Peterhoff et al, 2014). A characteristic, taxonspecific property of GGGPS is the oligomerization state, which can be dimeric or hexameric (Peterhoff et al, 2014;Linde et al, 2018). We used the same ASR protocol, but two different sets of recent GGGPS homologs to compute ancestors.…”
Section: Introductionmentioning
confidence: 99%